Does listening to music reduce anxiety and pain in third molar surgery?—a systematic review - Monteiro, João Luiz Gomes Carneiro; da Silva Barbirato, Davi; Moraes, Sandra Lúcia Dantas; Pellizzer, Eduardo Piza [UNESP]; do Egito Vasconcelos, Belmiro Cavalcanti (Springer Nature, 2022)
Objective: To perform a systematic review on the effects of listening to music in reducing preoperative anxiety and pain (intra or postoperative) in third molar extractions. Material and methods: A systematic review modeled according to the PRISMA guidelines was conducted. The MEDLINE/PubMed, Cochrane Library, Embase, and Scopus databases were searched for relevant reports. To be included in the study sample, the studies were required to be randomized controlled trials (RCT) on the effects of listening to music on outcomes of third molar extraction. Two reviewers independently extracted the relevant data from the reports. Results: A total of 1882 studies were retrieved after the duplicates were removed. After applying the inclusion criteria, five studies were included for qualitative analysis. In 4 studies, music was played before and during the extraction of the impacted third molars. In one study, music was played only before the procedure. The genres varied from classic piano music to rock, pop, jazz, folk, and even hymns. Overall, music listening was beneficial for patients in reducing preoperative anxiety or anxiety during the procedure compared to control. However, only one study demonstrated a statistically significant decrease in systolic blood pressure. Conclusions: Music may be an effective non-pharmacological measure to reduce preoperative anxiety in patients scheduled for third molar extraction; however, the hemodynamic effects and the effects on pain (both perioperative and postoperative) should be further explored. Clinical relevance: The side effects of certain medications may be avoided if listening to music is used in third molar extractions.
Keywords: Anxiety; Hemodynamics; Music; Third molar